The impact of exposure to news about electronic government surveillance on concerns about government intrusion, privacy self-efficacy, and privacy protective behavior. Issue 2 (2nd April 2016) - Mamonov, Stanislav; Koufaris, Marios
ABSTRACT: Government electronic surveillance programs are an active topic in public debates, yet little is known about how awareness of government electronic surveillance programs affects technology users' concerns, beliefs, and behaviors. This study examined the impact of exposure to news stories about government surveillance on users' concerns about government intrusion, their privacy self-efficacy, and the strength of passwords they use to protect information. Findings were that the exposure to news about government surveillance increases the level of concerns about government intrusion and has a negative impact on privacy self-efficacy. Further, contrary to expectations, this exposure also leads to weaker passwords used to protect information. Possible explanations and implications of the findings are discussed.